2000
DOI: 10.1002/1097-0142(20001101)89:9<1976::aid-cncr14>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of p16INK4a/p14ARF locus deletion and MDM-2 protein expression in adult acute myelogenous leukemia

Abstract: BACKGROUND. The p16 INK4a locus encodes two distinct proteins, p16 INK4a and p14 ARF . Although p16 INK4a and p15 INK4b are involved in the phosphorylation of the retinoblastoma (Rb) protein, p14 ARF interacts with the MDM-2 oncoprotein antagonizing its function as a suppressor of p53. The role of deletions of p16 INK4a /p14 ARF and p15 INK4b and expressions of MDM-2 in myeloid leukemias and its influence on prognosis remain unclear. METHODS. The authors analyzed deletions of p16 INK4 /p14 ARF and p15 INK4b in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…CDKN2A/B are frequently deleted in both adult and childhood ALL. Although numerous studies have been conducted thus far evaluating the prognostic significance of CDKN2A/B deletions in ALL patients, the correlation is still under debate [12][13][14][15][16][17][18]. Thus, it is valuable to perform a meta-analysis to comprehensively assess the association between CDKN2A/B deletions and clinical outcome in ALL patients.…”
Section: Discussionmentioning
confidence: 99%
“…CDKN2A/B are frequently deleted in both adult and childhood ALL. Although numerous studies have been conducted thus far evaluating the prognostic significance of CDKN2A/B deletions in ALL patients, the correlation is still under debate [12][13][14][15][16][17][18]. Thus, it is valuable to perform a meta-analysis to comprehensively assess the association between CDKN2A/B deletions and clinical outcome in ALL patients.…”
Section: Discussionmentioning
confidence: 99%
“…In de novo acute myeloid leukemia (AML), TP53 mutations are rare, occurring in less than 10% of patients (14)(15)(16)(17)(18). Although in some specific subsets of AML TP53 mutations are more frequent [for example, in up to 80% in patients with complex cytogenetics (19)], p53 inactivation more often results from the overexpression of its endogenous inhibitors MDMX or MDM2, which frequently occurs in p53 wild-type (WT) AML (20)(21)(22)(23)(24)(25)(26). It was recently reported that MDMX protein and mRNA are overexpressed in up to 92% of AML cases (27).…”
Section: Introductionmentioning
confidence: 99%
“…However, while these mutations are rare in MDS/AML with a normal karyotype (1%), they are seen in 40–50% of secondary and therapy-related cases [ 20 , 25 , 26 , 27 ], and in 80% of complex monosomal karyotypes (CK) that include 17p and/or 5q deletion [ 28 , 29 ]. Other inactivating mechanisms of wild-type p53 function include overexpression of MDM2 and MDM4, negative regulators of p53, in 20–30% and 40–50% of AML cases, respectively [ 30 , 31 , 32 , 33 , 34 ]. Unfortunately, treatment with Mdm2 inhibitors has not so far demonstrated a substantial effect in these cases [ 35 ].…”
Section: Characteristics Of Tp53 Mutations In Mds/amlmentioning
confidence: 99%